2020
DOI: 10.3389/fcell.2020.598622
|View full text |Cite
|
Sign up to set email alerts
|

RAB39B Deficiency Impairs Learning and Memory Partially Through Compromising Autophagy

Abstract: RAB39B is located on the X chromosome and encodes the RAB39B protein that belongs to the RAB family. Mutations in RAB39B are known to be associated with X-linked intellectual disability (XLID), Parkinson’s disease, and autism. However, the patho/physiological functions of RAB39B remain largely unknown. In the present study, we established Rab39b knockout (KO) mice, which exhibited overall normal birth rate and morphologies as wild type mice. However, Rab39b deficiency led to reduced anxiety and impaired learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 46 publications
9
36
2
Order By: Relevance
“…Zang et al [38] reported that Rab39b KO mice had cortical neurogenesis deficits, macrocephaly, and social and motor deficits. Similar behavioural performance was observed by Niu et al [39], demonstrating short-term working memory deficits, but the authors did not observe macrocephaly in agreement with our results. As suggested [39], this discrepancy may be caused by defects in metabolic or different biological processes between different genetic backgrounds (C57Bl/6J vs C57Bl/6N) or by the mouse age analysed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Zang et al [38] reported that Rab39b KO mice had cortical neurogenesis deficits, macrocephaly, and social and motor deficits. Similar behavioural performance was observed by Niu et al [39], demonstrating short-term working memory deficits, but the authors did not observe macrocephaly in agreement with our results. As suggested [39], this discrepancy may be caused by defects in metabolic or different biological processes between different genetic backgrounds (C57Bl/6J vs C57Bl/6N) or by the mouse age analysed.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning cognitive functions, Rab39b KO mice showed a slight deficit in the radial maze working memory task, which was also reported by Niu et al with different learning paradigms [39] and a drastic impairment in trace fear conditioning.…”
Section: Discussionsupporting
confidence: 81%
“…[Color figure can be viewed at wileyonlinelibrary.com] gene expression in mouse N2A cells a reduction in autophagolysosome formation has been observed, suggesting decreased autophagic flux. 124 When autophagy was induced with rapamycin, this impairment was eliminated, indicating that a loss of RAB39B expression impairs basal autophagy, but not autophagy induction. Notably, rapamycin treatment improved defects in synaptic plasticity and memory observed in RAB39B gene knockout mice, suggesting that autophagy plays a central role in phenotypes observed with RAB39B deficiency.…”
Section: Rab39b and Autophagymentioning
confidence: 99%
“…123 Despite the findings of these in vitro-based investigations, a recent study of RAB39B gene knockout mice has observed a reduction of postsynaptic NMDA receptor subunits as oppose to AMPA receptors, suggesting that in vivo deficits in synaptic function may differ from those established within in vitro models. 124…”
Section: Rab39b and Glutamatergic Receptor Maturation/modulationmentioning
confidence: 99%
See 1 more Smart Citation